Invasive Coronary Angiography in Patients with Native or Prosthetic Aortic Valve Endocarditis - Berger, Tim; Dees, Dominik; Siepe, Matthias; Pingpoh, Clarence; Fagu, Albi; Zeh, Wolfgang; Beyersdorf, Friedhelm; Neumann, Franz-Josef; Czerny, Martin; Kreibich, Maximilian (The Thoracic and Cardiovascular Surgeon, 2022)
Background Invasive coronary angiography (ICA) is essential to detect significant coronary artery disease (CAD) but is generally not recommended in patients with infective aortic valve endocarditis. This study aimed to evaluate the risks and benefits of preoperative ICA in patients before aortic valve replacement.Methods Between March 2008 and September 2020, 232 patients were surgically treated for infectious endocarditis of the aortic valve. Sixty-seven (29%) of them underwent preoperative diagnostic ICA and were compared with the patients without preoperative ICA. We collected their baseline characteristics, including the neurological status, previous cardiac surgical procedures, and reviewed the preoperative echocardiograms and the ICA data. The intraoperative data and clinical outcomes after ICA and after surgery were evaluated.Results ICA revealed a CAD in the majority of our patients (n = 36; 54%): One-vessel disease n = 19 (28%), two-vessel disease n = 6 (9%), and three-vessel disease n = 11 (16%). We observed no adverse events following preoperative diagnostic ICA, particularly no thromboembolic complications, including stroke, visceral, or lower body ischemia were detected. During surgical aortic valve replacement, concomitant coronary artery bypass grafting was performed in 20 patients (30%). In patients with preoperative ICA, postoperative in-hospital mortality was significantly lower (n = 8 [12%] vs. n = 30 [18%]; p < 0.001), while the incidence of postoperative bleeding was higher (n = 18 [27%] vs. n = 22 [13%]; p = 0.022). The new-onset stroke incidence was 5% in each group.Conclusion Taking a multidisciplinary team approach, ICA is safe in selected patients with aortic valve infectious endocarditis with no adverse clinical outcomes, but significant clinical implications.
Keywords: aortic valve endocarditis; coronary angiography; coronary artery disease; coronary bypass grafting